Composite material, lithium ion battery and electronic device
By using composite materials with ultramicropores and large pore volumes in lithium-ion batteries, adding N and P elements to form a porous rod-like structure, the problem of performance degradation of lithium-ion batteries at low and high temperatures is solved, and the circulation of batteries is improved Lifespan and stability in extreme environments.
Patent Information
- Application Number
- CN202411287686.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-13
- Publication Date
- 2024-12-17
AI Technical Summary
The increase in electrolyte viscosity of lithium-ion batteries under low temperature conditions leads to a decrease in conductivity and an increase in charge transfer impedance, which is manifested as low discharge capacity, increased internal resistance, unbalanced deintercalation of lithium, and obvious lithium evolution; electrochemical reaction under high temperature conditions The rate is accelerated, the consumption of electrolyte is intensified, and the cycle life is reduced.
A composite material with ultramicropores and large pore volume is used, and N elements and P elements are added to form a porous rod-like structure, which improves ionic conductivity, absorbs and stores electrolytes, slowly releases, reduces charge transfer impedance, and improves low- and high-temperature performance.
Effectively improve the low-temperature and high-temperature performance of lithium-ion batteries, extend the battery's cycle life, reduce the electrolyte consumption speed, and improve the battery's use stability in extreme environments.
Smart Images

Figure CN119143104A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemistry, and in particular to a composite material, a lithium-ion battery and an electronic device. Background Art
[0002] Lithium-ion batteries are widely used in electronic products such as electronic mobile devices, power tools and electric vehicles. People have increasingly higher requirements on the electrical performance of lithium-ion batteries in low and high temperature environments.
[0003] However, under low temperature conditions, the viscosity of the electrolyte increases or even partially solidifies, resulting in a decrease in the conductivity of the lithium-ion battery. At the same time, the compatibility between the electrolyte and the negative electrode active material and the separator deteriorates, resulting in a significant increase in the charge transfer impedance. Therefore, the performance of lithium-ion batteries at low temperatures is significantly reduced, which is specifically manifested in low discharge capacity, increased internal resistance, unbalanced lithium insertion and extraction, and obvious lithium precipitation. On the other hand, the electrochemical reaction rate of lithium-ion batteries accelerates under high temperature environments, electrolyte consumption intensifies, and the cycle life decreases rapidly. Therefore, how to improve the low-temperature and high-temperature performance of lithium-ion batteries has become an urgent problem to be solved. Summary of the invention
[0004] In view of this, the present application provides a composite material, a lithium-ion battery and an electronic device.
[0005] The first aspect of the present application provides a composite material, the chemical formula of the composite material is Li x C y O z N m P n Cl w , among which, 2.14≤x≤4.29, 1.67≤y≤3.33, 1.25≤z≤2.50, 0.36≤m≤1.79, 0.32≤n≤0.97, 0.85≤w≤1.13.
[0006] The present application adds N and P elements to a composite material with ultra-micropores and macropore volume, so that the composite material has a higher ionic conductivity, and the composite material of the present application has ultra-micropores slightly larger than desolvated lithium ions, which accelerates desolvation, reduces charge transfer impedance, and improves the low-temperature performance of lithium-ion batteries; the composite material of the present application is a porous rod-shaped structure, and its macropore volume structure can absorb and store electrolyte, increase the liquid retention, and slowly release it under high temperature conditions, which can slow down the consumption rate of electrolyte at high temperature and improve the cycle life of the battery. Therefore, when the above composite material is applied to the negative electrode plate, the high-temperature performance and low-temperature performance of the lithium-ion battery can be improved at the same time.
[0007] Based on the first aspect, in some possible implementations, based on the total mass of the composite material, the mass proportion of the P element is 10% to 30%, and the mass proportion of the N element is 5% to 25%.
[0008] When the content of N and P elements in the composite material is adjusted within the above range, the ionic conductivity of the composite material can be effectively improved, so that the lithium-ion battery has good low-temperature performance. In the present application, low temperature refers to a temperature less than or equal to 0°C.
[0009] Based on the first aspect, in some possible embodiments, the ionic conductivity of the composite material is 0.5 mS / cm to 8 mS / cm. When the ionic conductivity of the composite material is within the range of 0.5 mS / cm to 8 mS / cm, the charge transfer impedance can be effectively reduced, so that the lithium-ion battery has good low-temperature performance while also taking into account good high-temperature performance.
[0010] Based on the first aspect, in some possible implementations, the composite material has a porous structure, and the pore size measured by a nitrogen adsorption-desorption test is 0.4 nm to 1 nm.
[0011] The ultra-micropores in the composite material, which are slightly larger than the solvated lithium ions, can filter and accelerate desolvation, reduce charge transfer impedance, and improve the low-temperature performance of lithium-ion batteries. Moreover, when the pore size of the composite material is within the range of 0.4nm to 1nm, the desolvation effect is best, which is conducive to the embedding and extraction of lithium ions, further improving the low-temperature performance of lithium-ion batteries.
[0012] Based on the first aspect, in some possible embodiments, the composite material is a porous structure, and the pore volume measured by nitrogen adsorption-desorption test is 0.5 cm 3 / g to 1.2cm 3 / g. The ultra-micropores in the composite material can absorb and store electrolyte, increase the amount of liquid retained, and slowly release it under high temperature conditions to supplement the electrolyte inside the battery, thereby improving the high temperature performance and cycle life of the lithium-ion battery. Moreover, when the pore volume is 0.5cm 3 / g to 1.2cm 3 When the amount of electrolyte is within the range of 0.1477 W / g, the storage amount of electrolyte is within the most suitable range, which has a better effect on improving the high temperature performance of lithium-ion batteries.
[0013] Based on the first aspect, in some possible implementations, the length of the composite material is 0.5 μm to 50 μm, and the aspect ratio of the composite material is 1 to 100.
[0014] Based on the first aspect, in some possible implementations, the diameter of the composite material is 0.2 μm to 2 μm.
[0015] When the length, diameter and aspect ratio of the composite material of the present application are within a certain range, it has a positive effect on improving the high temperature performance and low temperature performance of the lithium ion battery.
[0016] Based on the first aspect, in some possible implementations, the cross-sectional shape of the composite material is a regular polygon.
[0017] The second aspect of the present application provides a method for preparing a composite material, comprising: dissolving a phosphate salt, a lithium salt, and methyltetramine in water to obtain a mixed solution; subjecting the mixed solution to a hydrothermal synthesis reaction to obtain an intermediate product; and carbonizing the intermediate product under an inert gas to obtain a composite material.
[0018] In the above preparation method, a composite material is prepared by dissolving a phosphate salt, a lithium salt and hexamethylenetetramine in water and heating them, and then adopting a hydrothermal synthesis method. The N element and the P element in the composite material are provided by the phosphate salt and the hexamethylenetetramine. The doping of the two impurity elements N and P makes the prepared composite material have high ionic conductivity. Furthermore, the lithium-ion battery has good low-temperature performance while also taking into account good high-temperature performance.
[0019] Based on the second aspect, in some possible implementations, the heating temperature is 100° C. to 300° C., the heating time is 6 h to 24 h, the carbonization temperature is 400° C. to 1200° C., and the carbonization time is 2 h to 8 h.
[0020] In the above preparation process, when the heating temperature, heating time, carbonization temperature and carbonization time meet a certain range, the ionic conductivity of the prepared composite material is higher. Furthermore, the lithium-ion battery has good low-temperature performance while also having good high-temperature performance.
[0021] Based on the second aspect, in some possible embodiments, the phosphate salt is phosphorus trichloride and / or phosphorus oxychloride. The phosphate salt provides the P element in the composite material, so that the prepared composite material has high ionic conductivity. Further, the lithium ion battery has good low temperature performance while also taking into account good high temperature performance.
[0022] Based on the second aspect, in some possible implementations, the lithium salt is at least one of lithium chloride, lithium nitrate, lithium sulfate, lithium acetate, and lithium phosphate. The above lithium salts can increase the content of lithium ions in the electrolyte.
[0023] The third aspect of the present application provides a lithium-ion battery, including a negative electrode plate, the negative electrode plate includes a negative electrode active material layer, the negative electrode active material layer includes the composite material provided in the first aspect of the present application, based on the total mass of the negative electrode active material layer, the mass proportion of the composite material is 0.5% to 2%.
[0024] When the composite material accounts for 0.5% to 2% of the total mass of the negative electrode active material layer, the lithium ion battery has good low temperature performance while also having good high temperature performance.
[0025] Based on the third aspect, in some possible implementations, based on the total mass of the negative electrode active material layer, the mass proportion of the P element is 0.05% to 0.6%, and the mass proportion of the N element is 0.025% to 0.5%.
[0026] When the P element accounts for 0.05% to 0.6% of the total mass of the negative electrode active material layer and the N element accounts for 0.025% to 0.5% of the total mass of the negative electrode active material layer, the lithium ion battery has good low temperature performance while also having good high temperature performance.
[0027] The fourth aspect of the present application provides an electronic device, including the lithium-ion battery provided in the third aspect of the present application. The lithium-ion battery has good low-temperature performance while also having good high-temperature performance, which is beneficial to improving the service life of the electronic device and the universality of the electronic device in high and low temperature environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a scanning electron microscope (SEM) photograph of the composite material in Example 1 of the present application.
[0029] Figure 2 This is a SEM photo of the negative electrode sheet in Example 1 of the present application.
[0030] Figure 3 This is a curve diagram of the impedance spectrum (EIS) test of the button-type lithium-ion battery at -20°C in Example 15 of the present application and Comparative Example 1.
[0031] Figure 4 This is a discharge test curve diagram of the single-layer all-electric laminated battery at 3.4V in Example 15 of the present application and Comparative Example 1.
[0032] Figure 5 This is a cycle capacity retention curve of the single-layer all-electric laminated battery in Example 15 of the present application and Comparative Example 1 at 45°C. DETAILED DESCRIPTION
[0033] The technical scheme in the embodiment of the present application is described clearly and in detail below. Obviously, the described embodiment is a part of the embodiment of the present application, rather than all the embodiments. Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application.
[0034] Composite Materials
[0035] One embodiment of the present application provides a composite material, the general formula of which is Li x C y O z N m P n Cl w , among which, 2.14≤x≤4.29, 1.67≤y≤3.33, 1.25≤z≤2.50, 0.36≤m≤1.79, 0.32≤n≤0.97, 0.85≤w≤1.13.
[0036] The present application adds N and P elements to a composite material with ultra-micropores and macropore volume, so that the composite material has a higher ionic conductivity, and the composite material of the present application has ultra-micropores slightly larger than desolvated lithium ions, which accelerates desolvation, reduces charge transfer impedance, and improves the low-temperature performance of lithium-ion batteries; the composite material of the present application is a porous rod-shaped structure, and its macropore volume structure can absorb and store electrolyte, increase the liquid retention, and slowly release it under high temperature conditions, slowing down the consumption rate of electrolyte at high temperature and improving the cycle life of the battery. Therefore, when the above composite material is applied to the negative electrode plate, the high-temperature performance and low-temperature performance of the lithium-ion battery can be improved at the same time.
[0037] In some embodiments, based on the total mass of the composite material, the mass proportion of the P element is 10% to 30%, and the mass proportion of the N element is 5% to 25%. For example, the mass proportion of the P element can be any value within the range of 10%, 15%, 20%, 25%, 30% or any value above; the mass proportion of the N element can be any value within the range of 5%, 10%, 15%, 20%, 25% or any value above.
[0038] When the content of N and P elements in the composite material is adjusted within the range of the present application, the ionic conductivity of the composite material can be effectively improved, so that the lithium-ion battery has good low-temperature performance while also taking into account good high-temperature performance. In the present application, low temperature refers to a temperature less than or equal to 0°C.
[0039] In some embodiments, the ionic conductivity of the composite material is 0.5 mS / cm to 8 mS / cm. For example, the ionic conductivity can be 0.5 mS / cm, 1 mS / cm, 1.5 mS / cm, 2 mS / cm, 2.5 mS / cm, 3 mS / cm, 3.5 mS / cm, 4 mS / cm, 4.5 mS / cm, 5 mS / cm, 5.5 mS / cm, 6 mS / cm, 6.5 mS / cm, 7 mS / cm, 7.5 mS / cm, 8 mS / cm, or any value in a range consisting of any of the above values.
[0040] When the ionic conductivity of the composite material is within the range of 0.5 mS / cm to 8 mS / cm, the charge transfer impedance can be effectively reduced, so that the lithium-ion battery has good low-temperature performance while also having good high-temperature performance.
[0041] In some embodiments, the composite material is a porous structure, and the pore size measured by nitrogen adsorption-desorption test is 0.4 nm to 1 nm. For example, the pore size can be 0.4 nm, 0.5 nm, 0.6 nm, 0.7 nm, 0.8 nm, 0.9 nm, 1 nm or any value in the range consisting of any of the above values.
[0042] The ultra-micropores in the composite material, which are slightly larger than the solvated lithium ions, can filter and accelerate desolvation, reduce charge transfer impedance, and improve the low-temperature performance of lithium-ion batteries. Moreover, when the pore size of the composite material is within the range of 0.4nm to 1nm, the desolvation effect is best, which is conducive to the embedding and extraction of lithium ions, further improving the low-temperature performance of lithium-ion batteries.
[0043] In some embodiments, the composite material has a porous structure, and the pore volume measured by nitrogen adsorption-desorption test is 0.5 cm 3 / g to 1.2cm 3 / g. For example, the pore volume can be 0.5cm 3 / g, 0.6cm 3 / g, 0.7cm 3 / g, 0.8cm 3 / g, 0.9cm 3 / g, 1cm 3 / g, 1.1cm 3 / g, 1.2cm 3 / g or any value within the range consisting of any of the above values.
[0044] The ultra-micropores in the composite material can absorb and store electrolyte, increase the amount of electrolyte, and slowly release it under high temperature conditions to replenish the electrolyte inside the battery, reduce the consumption rate of the electrolyte, increase the cycle life of the lithium-ion battery, and improve the high-temperature performance of the lithium-ion battery; and when the ultra-micropore volume is 0.5cm 3 / g to 1.2cm 3 When the electrolyte storage capacity is within the range of 1.5 ~ 2.0 g / cm2, the storage capacity of the electrolyte is within the most suitable range, which has a better effect on improving the high temperature performance of the lithium-ion battery.
[0045] In some embodiments, the length of the composite material is 0.5 μm to 50 μm. For example, the length can be 0.5 μm, 1 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm or any value in the range of any of the above values; the aspect ratio of the composite material is 1 to 100, for example, the aspect ratio can be 1, 5, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 50 or any value in the range of any of the above values.
[0046] In some embodiments, the diameter of the composite material is 0.2 μm to 2 μm. For example, the diameter can be 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2 μm, or any value in a range consisting of any of the above values.
[0047] When the length, diameter and aspect ratio of the composite material of the present application are within the range of the present application, it has a positive effect on improving the high temperature performance and low temperature performance of the lithium ion battery.
[0048] In some embodiments, the composite material is a rod-like structure, and the bottom of the rod-like structure is a regular polygon. The regular polygon can be at least one of a regular quadrilateral, a regular pentagon, a regular hexagon, a regular octagon, a regular decagon, a regular dodecagon, a regular tetradecagon, a regular hexadecagon, and a regular octagon.
[0049] The present application also provides a method for preparing a composite material, comprising: stirring and dissolving a phosphate salt, a lithium salt, and hexamethylenetetramine in water, then transferring and sweeping in a high-temperature reactor for heating treatment, and after completion, repeatedly filtering and washing with deionized water, and then placing in a 60°C oven for drying for 24 hours to obtain a powdered composite material, and transferring the dried composite material to a tubular furnace for carbonization treatment to prepare the composite material of the present application.
[0050] In the above preparation method, a composite material is prepared by dissolving a phosphate salt, a lithium salt and hexamethylenetetramine in water and heating them, and then adopting a hydrothermal synthesis method. The N element and the P element in the composite material are provided by the phosphate salt and the hexamethylenetetramine. The doping of the two impurity elements N and P makes the prepared composite material have high ionic conductivity. Furthermore, the lithium-ion battery has good low-temperature performance while also taking into account good high-temperature performance.
[0051] In some embodiments, the heating temperature is 100° C. to 300° C., the heating time is 6 h to 24 h, the carbonization temperature is 400° C. to 1200° C., and the carbonization time is 2 h to 8 h.
[0052] In some embodiments, hexamethylenetetramine can be replaced by formaldehyde, and water includes but is not limited to deionized water.
[0053] The inventors have found that in the above-mentioned preparation process, when the heating temperature, time and carbonization temperature, time meet the range of this application, the ionic conductivity of the prepared composite material is higher. Furthermore, the lithium-ion battery has good low-temperature performance while also having good high-temperature performance.
[0054] In some embodiments, the phosphate salt is phosphorus trichloride and / or phosphorus oxychloride. The above phosphate salt provides the P element in the composite material, so that the prepared composite material has high ionic conductivity. Further, the lithium ion battery has good low temperature performance while also taking into account good high temperature performance.
[0055] In some embodiments, the lithium salt is at least one of lithium chloride, lithium nitrate, lithium sulfate, lithium acetate, and lithium phosphate. The above lithium salts can increase the content of lithium ions in the electrolyte.
[0056] Negative electrode
[0057] The negative electrode sheet of the present application includes a negative electrode current collector and a negative electrode active material layer disposed on the negative electrode current collector. The negative electrode current collector may use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, etc., or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material layer includes a negative electrode active material, the composite material of the present application, and optionally a conductive agent, a binder and a thickener.
[0058] In some embodiments, based on the total mass of the negative electrode active material layer, the mass proportion of the composite material is 0.5% to 2%. For example, the mass proportion of the composite material can be 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2% or any value within the range of any of the above values.
[0059] When the composite material of the present application accounts for 0.5% to 2% of the total mass of the negative electrode active material layer, the lithium ion battery has good low temperature performance while also having good high temperature performance, and reduces the production cost of the lithium ion battery.
[0060] In some embodiments, based on the total mass of the negative electrode active material layer, the mass proportion of the P element is 0.05% to 0.6%, and the mass proportion of the N element is 0.025% to 0.5%. For example, the mass proportion of the P element can be 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6% or any value in the range of any of the above values. For example, the mass proportion of the N element can be 0.025%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, 0.5% or any value in the range of any of the above values.
[0061] By regulating the P element and the N element within the scope of the present application, the lithium-ion battery has good low-temperature performance while also having good high-temperature performance.
[0062] The specific type of negative electrode active material is not subject to specific restrictions and can be selected according to needs. As an example, the negative electrode active material includes but is not limited to natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO, Li-Sn alloy, Sn, Sn-O, SnO2, spinel structured Li4Ti5O 12 , Li-Al alloy.
[0063] The specific type of the conductive agent is not subject to specific restrictions and can be selected according to needs. As an example, the conductive agent includes but is not limited to conductive graphite, superconducting carbon, at least one of acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0064] The specific type of the binder is not subject to specific restrictions and can be selected according to needs. As an example, the binder includes but is not limited to at least one of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), water-based acrylic resin and carboxymethyl cellulose.
[0065] The specific type of thickener is not subject to specific restrictions and can be selected according to needs. As an example, the thickener includes but is not limited to sodium carboxymethylcellulose (CMC).
[0066] However, the present application is not limited to the above materials, and the negative electrode plate of the present application may also use other known materials that can be used as negative electrode active materials, conductive agents, binders and thickeners.
[0067] Isolation film
[0068] The material and shape of the separator used in the lithium-ion battery of the present application are not particularly limited, and can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0069] For example, the isolation film may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be selected.
[0070] A surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer can be a polymer layer or an inorganic layer, or a layer formed by a mixed polymer and an inorganic substance. The inorganic layer includes inorganic particles and a binder, and the inorganic particles are selected from at least one of aluminum oxide, silicon oxide, magnesium oxide, titanium oxide, hafnium dioxide, tin oxide, cerium dioxide, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide and barium sulfate. The binder is selected from at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride-hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyethylene alkoxy, polymethyl methacrylate, polytetrafluoroethylene and polyhexafluoropropylene. The polymer layer contains a polymer, and the material of the polymer is selected from at least one of polyamide, polyacrylonitrile, acrylate polymer, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyethylene alkoxy, polyvinylidene fluoride and poly (vinylidene fluoride-hexafluoropropylene).
[0071] Electrolyte
[0072] According to some embodiments of the present application, the electrolyte includes an organic solvent, a lithium salt and an optional additive. The organic solvent in the electrolyte of the present application may be any organic solvent known in the prior art that can be used as a solvent for the electrolyte. There is no restriction on the electrolyte used in the electrolyte of the present application, which may be any electrolyte known in the prior art. The additive of the electrolyte according to the present application may be any additive known in the prior art that can be used as an electrolyte additive. In some embodiments, the organic solvent includes, but is not limited to: ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), propylene carbonate or ethyl propionate. In some embodiments, the organic solvent includes an ether solvent, for example, including at least one of 1,3-dioxolane (DOL) and ethylene glycol dimethyl ether (DME). In some embodiments, the lithium salt includes at least one of an organic lithium salt or an inorganic lithium salt. In some embodiments, the lithium salt includes, but is not limited to, lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium bis(trifluoromethanesulfonyl)imide LiN(CF3SO2)2 (LiTFSI), lithium bis(fluorosulfonyl)imide Li(N(SO2F)2) (LiFSI), lithium bis(oxalatoborate) LiB(C2O4)2 (LiBOB), or lithium di(oxalatoborate) LiBF2(C2O4) (LiDFOB). In some embodiments, the additive includes at least one of fluoroethylene carbonate and adiponitrile.
[0073] Positive electrode
[0074] The positive electrode sheet includes a positive current collector and a positive active material layer disposed on the positive current collector. The positive current collector may be aluminum foil or nickel foil, etc., or may be any composite current collector disclosed in the prior art, for example, including but not limited to the current collector formed by combining the aforementioned conductive foil and the polymer substrate. The positive active material layer contains a positive active material, and the positive active material includes a compound that reversibly embeds and deintercalates lithium ions (i.e., a lithiated intercalation compound). In some embodiments, the positive active material may include a lithium transition metal composite oxide. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese and nickel. In some embodiments, the positive active material may include but is not limited to lithium cobaltate, lithium nickel manganese cobaltate, lithium nickel manganese aluminum, lithium iron phosphate, lithium vanadium phosphate, lithium cobalt phosphate, lithium manganese phosphate, lithium manganese iron phosphate, lithium iron silicate, lithium vanadium silicate, lithium cobalt silicate, lithium manganese silicate, spinel lithium manganese oxide, spinel lithium nickel manganese oxide and lithium titanate.
[0075] The positive electrode active material layer also includes a binder to bond the positive electrode active material particles to facilitate the formation of a film layer, and at the same time, it can also improve the bonding force between the positive electrode active layer and the positive electrode current collector. In some embodiments, the binder may include but is not limited to polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene butadiene rubber, acrylic (ester) styrene butadiene rubber, epoxy resin or nylon, etc. At least one of the above.
[0076] The positive electrode active material layer may also include a conductive material, including but not limited to a carbon-based material, a metal-based material, a conductive polymer, or any combination thereof. In some embodiments, the carbon-based material may include but is not limited to natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material may include but is not limited to metal powder or metal fiber, such as copper, nickel, aluminum, or silver. In some embodiments, the conductive polymer may be a polyphenylene derivative.
[0077] Lithium-ion battery
[0078] The lithium-ion battery of the present application also includes a shell (such as a packaging bag) for accommodating the above-mentioned positive electrode plate, separator, negative electrode plate and electrolyte, as well as other components known in the electrochemical field, and the present application does not limit the above-mentioned other components. The present application has no special restrictions on the shell, which can be a shell known in the art, as long as the purpose of the present application can be achieved. For example, an aluminum-plastic film packaging bag can be used. The present application has no special restrictions on the type of lithium-ion battery, which can include any device for electrochemical reaction. The lithium-ion battery containing the above-mentioned composite material has good low-temperature performance while also taking into account good high-temperature performance.
[0079] Electronic Devices
[0080] The lithium-ion battery is applied to an electronic device to power the load in the electronic device. Moreover, the lithium-ion battery has good low-temperature performance while also taking into account good high-temperature performance, which is beneficial to improving the service life of the electronic device and the universality in high and low temperature environments. Among them, the electronic device may include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini CD, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery and a lithium-ion capacitor, etc.
[0081] Example 1
[0082] <Preparation of composite materials>
[0083] Take 10g of phosphorus trichloride, 6g of lithium chloride, 20g of hexamethylenetetramine, and 400g of deionized water in a beaker, stir and dissolve, and then transfer to a 1000mL high-temperature reactor with a tetrafluoro lining, the heating temperature is 180°C, the heating time is 12h, and after the end, it is repeatedly filtered and washed with deionized water, and vacuum dried in a 60°C oven for 24h to obtain a powdered composite material; the dried composite material powder is transferred to a tubular furnace, the temperature is raised to 800°C at 2°C / min under nitrogen protection, and the temperature is kept for 2h to prepare the composite material of the present application.
[0084] <Preparation of negative electrode sheet>
[0085] Graphite, carbon nanotubes, sodium carboxymethyl cellulose (CMC-Na), styrene-butadiene rubber (SBR) and the above composite materials are uniformly dispersed in an appropriate amount of deionized water at a mass ratio of 97:1.2:1.3:0.5 to obtain a negative electrode slurry, wherein the solid content of the negative electrode slurry is 75wt%. The negative electrode slurry is uniformly coated on one surface of a current collector copper foil with a thickness of 10μm, and dried at 120°C to obtain a negative electrode sheet with a single-sided coating of a negative electrode active material layer with a coating thickness of 80μm. Repeat the above steps on the other surface of the copper foil to obtain a negative electrode sheet with a double-sided coating of a negative electrode active material layer. Dry under vacuum conditions at 120°C for 1 hour, and then obtain a negative electrode sheet with a specification of 78mm×875mm after cold pressing, cutting and slitting.
[0086] <Preparation of positive electrode sheet>
[0087] The positive electrode active material lithium cobalt oxide (LiCoO2), the conductive agent acetylene black, and the adhesive polyvinylidene fluoride (PVDF) are fully stirred and mixed in an appropriate amount of N-methylpyrrolidone (NMP) solvent at a mass ratio of 96.3:2.2:1.5 to form a uniform positive electrode slurry, wherein the solid content of the positive electrode slurry is 70wt%; the positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 10μm, and dried at 120℃ for 1 hour to obtain a positive electrode sheet coated with a positive electrode active material layer with a thickness of 60μm on one side. Repeat the above steps on the other surface of the aluminum foil to obtain a positive electrode sheet coated with a positive electrode active material layer on both sides. Dry under vacuum conditions at 120℃ for 1 hour, and then after cold pressing, cutting, and slitting, a positive electrode sheet with a specification of 74mm×867mm is obtained.
[0088] <Preparation of Electrolyte>
[0089] In an argon atmosphere glove box with a water content of less than 10ppm, non-aqueous organic solvents ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) are mixed in a mass ratio of EC: PC: EMC: DEC = 1: 3: 3: 3, and then fluoroethylene carbonate and 1,3-propane sultone are added, dissolved and fully stirred, and then lithium salt lithium hexafluorophosphate (LiPF6) is added, and the electrolyte is obtained after mixing evenly. Among them, based on the total mass of the electrolyte, the mass percentage of LiPF6 is 12.5%, the mass percentage of fluoroethylene carbonate is 2%, the mass percentage of 1,3-propane sultone is 2%, and the balance is non-aqueous organic solvent.
[0090] <Preparation of Separator Film>
[0091] A polyethylene porous polymer film with a thickness of 7 μm was used as the separator.
[0092] <Preparation of button cell>
[0093] The negative electrode was cut into Φ (diameter) = 14 mm discs as the working electrode, and a Φ (diameter) = 18 mm metal lithium sheet was used as the reference electrode. The two were separated by a Φ (diameter) = 20 mm isolation membrane, and an appropriate amount of electrolyte was added to assemble a CR2430 button-type lithium-ion battery.
[0094] <Preparation of single-layer all-electric stacked cells>
[0095] The negative electrode sheet was cut into an anode electrode with a tab area of 51×43.5mm, and the positive electrode sheet was cut into a cathode electrode with a tab area of 49.5×42mm. The two were separated by a 53×45.5mm isolation membrane, and an appropriate amount of electrolyte was added to assemble a standard XX5775 single-layer all-electric stacked battery.
[0096] Example 2 to Example 27
[0097] Except that the relevant preparation parameters in <Preparation of composite material> were adjusted according to Table 1, the other conditions / preparation method were the same as those in Example 1.
[0098] Comparative Example 1
[0099] Except that no composite material is added in <Preparation of Negative Electrode Plate>, other conditions / preparation methods are the same as those in Example 1.
[0100] Test Method
[0101] (1) Element content test
[0102] The Shimadzu / Kratos X-ray photoelectron spectrometer AXIS SUPRA+ was used to quantitatively test the N and P element contents in the negative electrode plates and composite materials.
[0103] (2) Electrochemical impedance spectroscopy (EIS) test
[0104] The British Solartron 1470E / 1455 electrochemical workstation was used for the electrochemical impedance spectroscopy test of button-type lithium-ion batteries at -20°C. The charge transfer internal resistance (Rct) was obtained by EIS refinement.
[0105] (3) High temperature cycle test of single-layer all-electric stacked battery
[0106] The high-temperature cycle performance is evaluated by the cycle capacity retention rate of the single-layer all-electric laminated battery. The single-layer all-electric laminated battery after formation is placed in a constant temperature environment of 45°C, charged to 4.52V at a constant current of 0.7C, and then charged to a cut-off current of 0.05C at a constant voltage. After full charge, it is left to stand for 3 minutes, and then discharged to 3.0V at 0.5C. The discharge capacity is recorded as D0, and then a cycle test of 0.7C charging / 0.5C discharge is performed for 100 cycles. The discharge capacity after the 100th cycle is D1. The cycle capacity retention rate (%) of the single-layer all-electric laminated battery after 100 cycles at high temperature (45°C) = D1 / D0×100%.
[0107] (4) High and low temperature discharge test of single-layer all-electric stacked batteries
[0108] The formed single-layer all-electric stacked battery was placed in a constant temperature environment of 25°C, charged to 4.52V at a constant current of 0.7C, and then charged to a cut-off current of 0.05C at a constant voltage. After full charge, it was left to stand for 3 minutes and the furnace was adjusted.
[0109] Warm to {25, 35, 45, 60, 10, 0, -10, -15, -20} °C; stand for 240 min, then discharge to 3.0 V at 0.2 C. Repeat the above steps and test all temperatures according to the temperature conditions in sequence. The ratio of the discharge capacity at different temperatures to the discharge capacity at 25 °C is the high and low temperature discharge capacity retention rate.
[0110] (5) Test of scanning electron microscope
[0111] Use a Nova Nano SEM 450 scanning electron microscope (SEM) to characterize the cross-sectional morphology of the composite material and the negative electrode sheet. The gold spraying time before sample testing is 20 s, and the scanning voltage during testing is 10 kV.
[0112] (6) Test of pore structure
[0113] Use a Micromeritics physical adsorption instrument produced by the United States to characterize the pore size structure of the material. Before sample testing, it needs to be vacuum activated at 200 - 250 °C for at least 6 h to remove the adsorbed water vapor and impurities in the pores. The activated sample is tested in a liquid nitrogen environment at -196 °C to obtain the N2 adsorption - desorption isotherm. Using the Brunauer - Emmett - Teller (BET) method, select the test points within the relative pressure range of 0.05 < P / P0 < 0.30 to calculate the specific surface area (SBET) of the sample, and take the single - point adsorption volume at P / P0 = 0.95 to calculate the total pore volume of the sample. When the pore size of the material is smaller than the N2 molecular size, CO2 can be selected as the probe molecule for pore structure characterization at 0 °C, and the DFT method is used to calculate the pore size distribution of the sample, and calculate the pore volume contributed by ultra - micropores with pore size < 1 nm and the pore volume contributed by micropores with pore size < 2 nm.
[0114] (7) Test of ionic conductivity
[0115] Calculation of ionic conductivity: Place 100 mg of the composite material powder in a die cell, apply a pressure of 380 MPa, hold the pressure for 1 minute, then attach indium sheets on both sides of the electrolyte sheet as blocking electrodes, and apply a certain pressure for AC impedance testing. The frequency range of the impedance test is from 1 Hz to 3 MHz, and the amplitude voltage is 50 mV. The obtained resistance result is used to calculate the ionic conductivity according to the formula σ = L / (R×S). Among them, S is the cross - sectional area, L is the thickness, and R is the measured resistance value. The ionic conductivity of the composite material is tested at different temperatures.
[0116] Figure 1 It is the scanning electron microscope image of the composite material in Example 1. It can be seen from Figure 1 that the composite material is in a rod - like structure.
[0117] Figure 2This is a scanning electron microscope image of the negative electrode sheet in Example 1. Figure 2 It can be seen that the rod-like structured composite material is embedded in the negative electrode sheet.
[0118] Figure 3 The following are the impedance spectroscopy (EIS) test diagrams of the button-type lithium-ion batteries in Example 15 and Comparative Example 1 at -20°C. Figure 3 It can be seen that after adding the composite material of the present application to the button-type lithium-ion battery, the charge transfer impedance is effectively reduced, and the low-temperature performance of the lithium-ion battery is further improved.
[0119] Figure 4 The 3.4V discharge test curve of the single-layer all-electric laminated battery in Example 15 and Comparative Example 1 is shown. Figure 4 It can be seen that compared with Comparative Example 1, after the composite material of the present application is added to the single-layer all-electric laminated battery of Example 15, the cycle capacity retention rate of the battery is significantly improved at low temperature (-20°C), further improving the low temperature performance of the battery.
[0120] Figure 5 The 45°C cycle capacity retention curve of the single-layer all-electric laminated battery in Example 15 and Comparative Example 1 is shown. Figure 5 It can be seen that after the single-layer all-electric laminated battery in Example 15 is added with the composite material of the present application, the cycle capacity retention rate of the single-layer all-electric laminated battery at high temperature is improved.
[0121] Among them, the preparation conditions of Example 1 to Example 27 are recorded in Table 1.
[0122] Table 1
[0123]
[0124]
[0125] The relevant performance parameters of Examples 1 to 27 and Comparative Example 1 are recorded in Table 2.
[0126] Table 2
[0127]
[0128]
[0129] Note: “ / ” in Table 2 means there is no corresponding substance or parameter.
[0130] It can be seen from Table 1 and Table 2 that, compared with Comparative Example 1, the high temperature performance and low temperature performance of the lithium ion battery are significantly improved by adding the composite material of the present application to Examples 1 to 27.
[0131] In Examples 1 to 6, different types of phosphate salts and lithium salts are used as reactants to prepare the composite materials of the present application. Since they can provide the N element and the P element in the composite materials of the present application, the prepared composite materials have high ionic conductivity and improve the low-temperature performance of lithium-ion batteries.
[0132] In Examples 7 to 14, changing the heating temperature, heating time, carbonization temperature, and carbonization time will affect the high temperature performance and low temperature performance of the lithium ion battery.
[0133] Compared with Example 13, Examples 15 to 17 affect the high temperature performance and low temperature performance of the lithium ion battery by changing the mass proportion of the composite material in the negative electrode active material layer.
[0134] From the data in Table 1 and Table 2, it can be seen that the high temperature performance and low temperature performance of the lithium ion battery in Example 15 are significantly improved, the impedance value of the lithium ion battery at -20 degrees Celsius in Example 15 is significantly reduced, the cycle capacity retention rate of the lithium ion battery at -20 degrees Celsius is significantly improved, and the low temperature performance of the lithium ion battery is significantly improved. The ionic conductivity of the composite material in Example 15 reaches the maximum value (8mS / cm), and the pore volume also reaches the maximum value (1.2cm 3 / g), maximizes the amount of liquid retained, can be slowly released under high temperature conditions, replenishes the electrolyte inside the battery, reduces the consumption rate of the electrolyte, increases the cycle life of the lithium-ion battery, and improves the high-temperature performance of the lithium-ion battery.
[0135] In Examples 18 to 27, when the heating temperature, heating time, carbonization temperature, carbonization time and the mass proportion of the composite material in the negative electrode active material layer are changed and are not within the range of the original conditions, the high temperature performance and low temperature performance of the lithium ion batteries of Examples 18 to 27 are slightly reduced compared to Example 1; however, compared to Comparative Example 1, the lithium ion battery still has good high temperature performance and low temperature performance. It can be seen that when preparing the composite material of the present application, the following conditions are met: the heating temperature is 100°C to 300°C, the heating time is 6h to 24h, the carbonization temperature is 400°C to 1200°C, the carbonization time is 2h to 8h, and the mass proportion of the composite material in the negative electrode active layer is 0.5% to 2%, the prepared lithium ion battery has better high temperature performance and low temperature performance.
[0136] The above implementation modes are only used to illustrate the technical solution of the present application and are not intended to limit it. Although the present application is described in detail with reference to the above implementation modes, a person skilled in the art should understand that the technical solution of the present application may be modified or replaced by equivalents without departing from the scope of the technical solution of the present application.
Claims
1. A composite material, characterized in that: The general chemical formula of the composite material is Li x C y O z N m P n Cl w , 2.14≤x≤4.29, 1.67≤y≤3.33, 1.25≤z≤2.50, 0.36≤m≤1.79, 0.32≤n≤0.97, 0.85≤w≤1.
13.
2. The composite material according to claim 1, characterized in that Based on the total mass of the composite material, the mass proportion of the P element is 10% to 30%, and the mass proportion of the N element is 5% to 25%.
3. The composite material according to claim 1, characterized in that The composite material has an ionic conductivity of 0.5 mS / cm to 8 mS / cm.
4. The composite material according to claim 1, characterized in that The composite material also satisfies at least one of the following conditions: (1) The composite material has a porous structure, and the pore size measured by nitrogen adsorption-desorption test is 0.4 nm to 1 nm; (2) The composite material has a porous structure, and the pore volume measured by nitrogen adsorption-desorption test is 0.5 cm 3 / g to 1.2cm 3 / g; (3) The length of the composite material is 0.5 μm to 50 μm, and the aspect ratio of the composite material is 1 to 100; (4) The cross-section of the composite material is in the shape of a regular polygon.
5. A method for preparing a composite material according to any one of claims 1 to 4, characterized in that: include: Dissolving a phosphate salt, a lithium salt and hexamethylenetetramine in water to obtain a mixed solution; Performing a hydrothermal synthesis reaction on the mixed solution to obtain an intermediate product; The intermediate product is carbonized under an inert gas to obtain the composite material.
6. The method for preparing the composite material according to claim 5, characterized in that: The preparation method also satisfies at least one of the following conditions: (1) The temperature of the hydrothermal synthesis reaction is 100° C. to 300° C., and the time of the hydrothermal synthesis reaction is 6 h to 24 h; (2) The carbonization temperature is 400° C. to 1200° C., and the carbonization time is 2 h to 8 h.
7. The method for preparing a composite material according to claim 5, characterized in that: The preparation method also satisfies at least one of the following conditions: (1) The phosphate salt is phosphorus trichloride and / or phosphorus oxychloride; (2) The lithium salt is at least one of lithium chloride, lithium nitrate, lithium sulfate, lithium acetate, and lithium phosphate.
8. A lithium-ion battery, comprising a negative electrode plate, wherein the negative electrode plate comprises a negative electrode active material layer, characterized in that: The negative electrode active material layer comprises the composite material according to any one of claims 1 to 4, and based on the total mass of the negative electrode active material layer, the mass proportion of the composite material is 0.5% to 2%.
9. The lithium ion battery according to claim 8, characterized in that Based on the total mass of the negative electrode active material layer, the mass proportion of the P element is 0.05% to 0.6%, and the mass proportion of the N element is 0.025% to 0.5%.
10. An electronic device, characterized in that: The electronic device comprises the lithium-ion battery according to claim 8 or 9.
